CD8+ T‐Lymphocyte–Driven Limbic Encephalitis Results in Temporal Lobe Epilepsy. Issue 4 (15th January 2021) - Pitsch, Julika; van Loo, Karen M. J.; Gallus, Marco; Dik, Andre; Kamalizade, Delara; Baumgart, Ann‐Kathrin; Gnatkovsky, Vadym; Müller, Johannes Alexander; Opitz, Thoralf; Hicking, Gordon; Naik, Venu Narayanan; Wachsmuth, Lydia; et al.
Abstract : Objective: Limbic encephalitis (LE) comprises a spectrum of inflammatory changes in affected brain structures including the presence of autoantibodies and lymphoid cells. However, the potential of distinct lymphocyte subsets alone to elicit key clinicopathological sequelae of LE potentially inducing temporal lobe epilepsy (TLE) with chronic spontaneous seizures and hippocampal sclerosis (HS) is unresolved. Methods: Here, we scrutinized pathogenic consequences emerging from CD8 + T cells targeting hippocampal neurons by recombinant adeno‐associated virus‐mediated expression of the model‐autoantigen ovalbumin (OVA) in CA1 neurons of OT‐I/RAG1 −/− mice (termed "OVA‐CD8 + LE model"). Results: Viral‐mediated antigen transfer caused dense CD8 + T cell infiltrates confined to the hippocampal formation starting on day 5 after virus transduction. Flow cytometry indicated priming of CD8 + T cells in brain‐draining lymph nodes preceding hippocampal invasion. At the acute model stage, the inflammatory process was accompanied by frequent seizure activity and impairment of hippocampal memory skills. Magnetic resonance imaging scans at day 7 of the OVA‐CD8 + LE model revealed hippocampal edema and blood–brain barrier disruption that converted into atrophy until day 40. CD8 + T cells specifically targeted OVA‐expressing, SIINFEKL‐H‐2K b –positive CA1 neurons and caused segmental apoptotic neurodegeneration, astrogliosis, and microglial activation. At the chronic model stage, mice exhibited spontaneous recurrent seizures and persisting memory deficits, and the sclerotic hippocampus was populated with CD8 + T cells escorted by NK cells. Interpretation: These data indicate that a CD8 + T‐cell–initiated attack of distinct hippocampal neurons is sufficient to induce LE converting into TLE‐HS. Intriguingly, the role of CD8 + T cells exceeds neurotoxic effects and points to their major pathogenic role in TLE following LE. ANN NEUROL 2021;89:666–685